Pre-school libraries ; a survey of services on reading promotion and literature awareness of children - Tabique, Vita Angeli Philein V.; Dela Torre, Nathalie N. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2006)
The education of young Filipino children has been given much importance over the years. This can be seen in the growth of schools offering preschool levels. Equally apparent is the proliferation of independent or exclusive preschools that are not affiliated to larger educational institutions.
The rapid increase in the number of this type of preschool and the possibility that preschool education be made compulsory has placed pressure on those who are concerned with the education of young children. The need to provide them with excellent and appropriate learning experiences, activities and services has escalated. With this in mind, one question to ask would be what are these preschools doing to promote the reading and literature awareness of children. This study is an exploration of the activities and services preschools provide to encourage reading and literature awareness among pupils. The preschools included in this study were privately owned, exclusively catering to children from birth to six years old and operating within the vicinity of the 4th District of Quezon City. Preschool administrators, library personnel and teachers of Communication Skills or Language arts were surveyed.
The descriptive-survey method of research was used. Three sets of constructed questionnaires composed of open-ended, multiple choice and yes-no questions were used as research instruments. The gathered data were then recorded and evaluated through the use of frequency distribution.
The results of the study showed that preschool administrators view the library, its book collection and services as substantially significant to the promotion of reading and literature awareness and to the overall education of children. The services rendered by library personnel to specifically promote reading and literature awareness were storytelling, guided reading, group-reading, and group-research sessions.
Findings also revealed that majority of the teachers provide a wide collection of books in the classroom and read aloud to the pupils on a regular basis.
The aforementioned library services and teaching practices are recommended to promote reading and literature awareness of pupils. Preschools and their libraries are further recommended to provide additional services. These are to offer regular schedules for class visits to the library and to include parents in the library and literature program.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Libraries and preschool children -- Philippines -- Quezon City; Reading promotion -- Philippines -- Quezon City; Literature awareness -- Philippines -- Quezon City